Pandangan Hukum Islam tentang Buruh: Studi Historis di Indonesia - Muhammad Aiz (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2011)
This paper will explain the views of Islamic law on labor. Studies conducted for the historical development of workers in Indonesia. From this paper can be concluded that the partisanship of Islam to the union of labor is not without reason, because labor is a social community that is quite vulnerable exploited by employers or owners of capital. Many cases we encounter the story of workers who receive unfair treatment from employers. Many examples of related issues associated with the injustice of employers to the workers. Because of the vulnerable status of this, Islam long ago have given general guidelines about the concept of labor, so workers get fair treatment from employers and authorities. Islamic guidance is reflected in the Qur’an, as quoted in the letter of Surah al-Ahqaf: 19, which describes the award, so employers pay attention to the workers according to the quality of his work with the welfare approach. In a hadith the Prophet, also explained that the employer must pay wages before his sweat dries.